2018
DOI: 10.1111/1346-8138.14605
|View full text |Cite
|
Sign up to set email alerts
|

Serum 5‐S‐cysteinyldopa behavior in the early phase of nivolumab treatment of 12 melanoma patients

Abstract: Along with the expansion of therapeutic options for metastatic melanoma, the development of useful biomarkers is urgently required to predict and monitor treatment response. Serum 5-S-cysteinyldopa (5-S-CD) has been identified as a diagnostic marker of malignant melanoma, but its utility as a biomarker for emerging therapeutic agents remains unknown. We assessed serum 5-S-CD in 12 metastatic melanoma patients (median age, 76 years; six men and six women) who had been treated with nivolumab (Nivo) at Shinshu Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Omodaka et al examined serum levels of 5SCD in 12 metastatic melanoma patients [100] and compared 5SCD and LDH levels measured before and after 3-6 weeks of treatment with nivolumab (Nivo) and their changes with the clinical responses. A decrease of 10 nmol/L or more of serum 5SCD was observed only in partial response patients (2/3 cases, 67%), while an increase of 10 nmol/L or more of serum 5SCD was seen only in progressive disease patients (4/8 cases, 50%).…”
Section: Usefulness Of 5scd In Monitoring Treatments For Melanomamentioning
confidence: 99%
See 1 more Smart Citation
“…Omodaka et al examined serum levels of 5SCD in 12 metastatic melanoma patients [100] and compared 5SCD and LDH levels measured before and after 3-6 weeks of treatment with nivolumab (Nivo) and their changes with the clinical responses. A decrease of 10 nmol/L or more of serum 5SCD was observed only in partial response patients (2/3 cases, 67%), while an increase of 10 nmol/L or more of serum 5SCD was seen only in progressive disease patients (4/8 cases, 50%).…”
Section: Usefulness Of 5scd In Monitoring Treatments For Melanomamentioning
confidence: 99%
“…The result of Nivo was determined as progressive disease. This Figure was modified with the consent of authors (Omodaka et al,[100]).…”
mentioning
confidence: 99%
“…Analyzing 12 metastatic MM patients under nivolumab therapy, they showed that serum 5-S-CD levels decreased in 2 of 3 patients having a partial response and increased in 4 of 8 progressive cases. 20 Their results suggest the possible monitoring efficacy of 5-S-CD in the early phase of nivolumab therapy. On the other hand, the present study showed the utility of 5-S-CD as a predictive marker for the efficacy of long-term nivolumab therapy.…”
Section: Discussionmentioning
confidence: 96%
“…The results of the present study showed that among patients with advanced MM who underwent nivolumab therapy, baseline serum 5-S-CD levels >25.0 nmol/L were able to significantly predict poor prognosis. Recently, Omodaka et al 20 also described that serum 5-S-CD levels in the early treatment phase (3–6 weeks after initial administration of nivolumab) could possibly predict therapeutic responses in metastatic MM. Analyzing 12 metastatic MM patients under nivolumab therapy, they showed that serum 5-S-CD levels decreased in 2 of 3 patients having a partial response and increased in 4 of 8 progressive cases.…”
Section: Discussionmentioning
confidence: 99%
“…[ 35 ] Other reports showed that the lactate dehydrogenase and 5-S-CD combination may predict the response to dacarbazine treatment [ 36 ] and anti-programmed death-1 antibody therapy. [ 37 ] These findings indicate that it is very important to evaluate multiple factors in various combinations. This study was conducted in a small cohort of Japanese patients, and therefore it is necessary to explore the utility of the triple marker in a large cohort of different patient groups.…”
Section: Discussionmentioning
confidence: 99%